Comparative study on corneal epithelium healing: effects of crosslinked hyaluronic acid and amniotic membrane extract eye drops in rats - Gonçalves e Souza, Lenara; Vilardo Lóes Moreira, Matheus; Sayuri Saçaki, Claudia; Perlmann, Eduardo; Guimarães Lopes, Thacyana Beatriz; Ferreira, Enio; Moreno, Juan Carlos Duque; Montiani-Ferreira, Fabiano (Frontiers in Veterinary Science, 2024)
Introduction: Corneal ulcer is a common lesion in human and veterinary medicine. Few investigations have evaluated the efficacy of cross-linked hyaluronic acid (X-HA) eye drops on corneal wound healing. In addition, this is the first study to demonstrate and compare the efficacy amniotic membrane extract eye drops (AMEED) to X-HA for corneal wound healing in rats. Material and Methods: Fifteen male Wistar rats (30 eyes) were used for this study. Ten eyes were treated with X-HA, AMEED, or 0.9% saline. After general and topical anesthesia, a superficial corneal ulcer was created using a corneal trephine. The defect was further polished with a diamond burr. Three groups of ten eyes each were treated with either one drop of 0.75% X-HA or AMEED or 0.9% saline (control), instilled every 12 hours for 72 hours. Median epithelial defect area (MEDA), % of the total corneal surface, was measured at 0, 12, 24, 36, 48, and 72 hours. Re-epithelization time scores also were evaluated. The Kruskal-Wallis test was used to compare the median times for re-epithelization and histopathologic scores between groups. Friedman test (for paired data) was employed to compare results from the serial analysis of MEDA and vascularization scores between groups. Results: MEDA was not significantly different between X-HA and AMEED. MEDA was significantly smaller in the X-HA group, compared to control group at 36h and 48 hours: 2.73 IQR 5.52% x 9.95 IQR 9.10%, P=0.024 and 0.00 IQR 0.26% x 6.30 IQR 8.54%, P=0.030, respectively. An overall significantly lower time for re-epithelization was observed in the group treated with X-HA (3.00 IQR 3.00) compared to AMEED (6.5 IQR 3.00) and control (7.00 IQR 1.00), P=0.035. Vascularization, hydropic degeneration, and epithelial-stromal separation were significantly less observed in samples treated with X-HA group, compared to AMEED and saline-treated samples. Significantly more corneal epithelium cells were labelled for caspase 3 in samples from AMEED and saline-treated groups compared to X-HA. Discussion: Topical X-HA has been shown to accelerate corneal epithelial healing. AMEED did not decrease corneal reepithelialization time. X-HA may also potentially be used as an adjunct therapy for treating corneal ulcers in clinical situations.